Chronic proximal spinal muscular atrophy of childhood and adolescence: sex influence. Issue 6 (December 1984) - Hausmanowa-Petrusewicz, I; Zaremba, J; Borkowska, J; Szirkowiec, W
Abstract : Segregation analysis was performed on 354 cases of chronic proximal spinal muscular atrophy of childhood and adolescence (CPSMA) in the total series and in a number of subgroups formed according to the age at onset and sex. The analysis provided evidence of sex influence in the series studied, particularly in a subgroup of the milder form of the disease with onset between the 37th month and 18th year of life. In the latter subgroup, females were affected much less frequently. This was particularly striking after age at onset of 8 years, and only exceptionally were females affected after the age of 13 years. These facts point to incomplete penetrance of the gene.